Frontiers of the Ecology of Subjectivity - Mikko Snellman (Aalto University, School of Arts, Design and Architecture, Department of Art, 2022)
In my visual essay I try to enlighten pedagogical space, art making space and the space of research with affectivity and new materialistic approaches. In this I use mainly philosophy of the French thinkers (Gilles Deleuze and Félix Guattari) and concepts like affect, becoming-other, striated and smooth space, ecology of subjectivity and . The small art school for children and young people in the remote village in South Ostrobothnia in Finland (Kauhajoki) and contemporary art workshop and in this very workshop the performance art experimentation will all form peripheries of art and education.  I will look at  questions of subjectivity and ecology through the case of performance in the workshop. Performance art and other fields of contemporary art requires the ability to throw oneself towards the unknown. Art has always the strong bridge to the material contexts, environments, spaces around us. And even more: we are in the deep continuum of materiality-mentality-sociality with art. This forms also our subjectivity, even temporarily, even much before identity. Art offers ways for us to reinvent ourselves in  new subjectivities which can be surprising, uncontrollable and yet-unkown to us.